AIDSVu Cities' Progress Toward HIV Care Continuum Goals: Cross-Sectional Study - Nicole Hood; Nanette Benbow; Chandni Jaggi; Shamaya Whitby; Patrick Sean Sullivan (JMIR Publications, 2024)
BackgroundPublic health surveillance data are critical to understanding the current state of the HIV and AIDS epidemics. Surveillance data provide significant insight into patterns within and progress toward achieving targets for each of the steps in the HIV care continuum. Such targets include those outlined in the National HIV/AIDS Strategy (NHAS) goals. If these data are disseminated, they can be used to prioritize certain steps in the continuum, geographic locations, and groups of people. ObjectiveWe sought to develop and report indicators of progress toward the NHAS goals for US cities and to characterize progress toward those goals with categorical metrics. MethodsHealth departments used standardized SAS code to calculate care continuum indicators from their HIV surveillance data to ensure comparability across jurisdictions. We report 2018 descriptive statistics for continuum steps (timely diagnosis, linkage to medical care, receipt of medical care, and HIV viral load suppression) for 36 US cities and their progress toward 2020 NHAS goals as of 2018. Indicators are reported categorically as met or surpassed the goal, within 25% of attaining the goal, or further than 25% from achieving the goal. ResultsCities were closest to meeting NHAS goals for timely diagnosis compared to the goals for linkage to care, receipt of care, and viral load suppression, with all cities (n=36, 100%) within 25% of meeting the goal for timely diagnosis. Only 8% (n=3) of cities were >25% from achieving the goal for receipt of care, but 69% (n=25) of cities were >25% from achieving the goal for viral suppression. ConclusionsDisplay of progress with graphical indicators enables communication of progress to stakeholders. AIDSVu analyses of HIV surveillance data facilitate cities' ability to benchmark their progress against that of other cities with similar characteristics. By identifying peer cities (eg, cities with analogous populations or similar NHAS goal concerns), the public display of indicators can promote dialogue between cities with comparable challenges and opportunities.